Role of Inflammation and Motility Disorders in the Development, Course and Consequences of Functional Gastrointestinal and Biliary Tract Diseases (Literature Review and Expert Panel Resolution) - V. T. Ivashkin; D. S. Bordin; T. L. Lapina; M. A. Livzan; A. V. Okhlobystin; E. A. Poluektova; A. S. Trukhmanov; Yu. P. Uspenskiy; Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to present the results of the Expert Panel with a discussion of modern concepts of the pathogenesis of functional gastrointestinal diseases and the possibilities of multitarget therapy with trimebutine.   Key points. Low-grade inflammation can be considered as a morphological substrate of functional diseases with an increase in activated mastocytes and eosinophils, T-helpers 2 and T-helpers 17 in the gastrointestinal mucosa. In the development in the content of visceral hypersensitivity, the functional connection between mastocytes and TRPV1-positive sensory endings of the vagus nerve is of great importance. Proinflammatory cytokines and matrix metalloproteinases can enter the systemic circulation, provoking the development of systemic manifestations. Increased levels of proinflammatory cytokines are supported by altered intestinal permeability and microbiota. Functional diseases are believed to modify the symptoms and course of concomitant organic diseases of the gastrointestinal tract (for example, functional diseases of the biliary tract may contribute to the development of cholelithiasis, pancreatitis). The peripheral μ-, κ- and δ-receptor agonist trimebutine (Trimedat®) regulates the production of enterohormones, modulates motility throughout the gastrointestinal tract and normalizes visceral sensitivity. The effectiveness of trimebutine in the treatment of functional disorders has been shown in various studies. Trimebutine helps reduce the production of proinflammatory cytokines, including interleukin-6.   Conclusion. In the treatment of functional diseases of the gastrointestinal tract, trimebutine can be considered as a multitarget agent, since the drug helps to normalize motility, reduces the degree of visceral hypersensitivity, exhibits anti-inflammatory and neuroregenerative effects, and can also increase the effectiveness of treatment of concomitant diseases.